DETECTION OF MARKERS OF HERPES VIRUS INFECTION AND PNEUMOCYSTOSIS IN CHILDREN FROM HIV-INFECTED MOTHERS - P. A. Savinkov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. Study the role of herpes viruses and pneumocystis in infectious complications in children from HIV-infected mothers. Materials and methods. Sera and blood cells from 59 children from HIV-infected mothers were studied for the presence of various markers of herpes virus infections and pneumocystosis by a complex of methods of modem laboratory diagnostics. Results. Frequency of detection of markers of herpes virus infection was from 10% for chicken pox in children with non-final HIV test to 93% for herpes simplex virus in HIV-infected children from closed organized groups. Signs of active infection in children with laboratory confirmed HIV infection were diagnosed 2.5 times more frequently for HSV infection and chicken pox and 1.8 times more frequently for HHV-6 and pneumocystis than in children with non-final HIV test. Markers of various disease stages with opportunistic infections (01) were detected in children with confirmed HIV-infection: primary acute and latent forms of the infection, reactivation, reconvalescence, whereas in children with non-final HIV test maternal antibodies against herpes virus and pneumocystis predominated. Markers of active infections excluding HSV and HHV-6 were more frequently detected in children from families than in children from closed organized groups. Conclusion. The feature detected - a lower percentage of detection of markers of active forms of 01 in HI V-infected children from social institutions - is determined by the fact that observation of these children is carried out by medical personnel that have the knowledge and experience of prophylaxis of infectious complications in HIV-infected children, whereas quality anti-epidemic regimen is frequently not maintained regarding home children with HIV infection. Another factor facilitating spread of opportunistic infections is the asocial lifestyle of most of the examined families. These data dictate the necessity of enhancement of anti-epidemic regimen and prophylaxis of opportunistic infections in family loci. Not only HIV-infected children, but also all the family members should be examined for markers of herpes virus infection and pneumocystosis in order to detect sources of the infection and timely execution of the prophylaxis measures.